Seasonal and environmental factors contribute to the variation in the gut microbiome : A large-scale study of a small bird - Liukkonen, Martta; Muriel, Jaime; Martínez-Padilla, Jesús; Nord, Andreas; Pakanen, Veli-Matti; Rosivall, Balázs; Tilgar, Vallo; van Oers, Kees; Grond, Kirsten; Ruuskanen, Suvi (Wiley-Blackwell, 2025)
Environmental variation can shape the gut microbiome, but broad/large-scale data on among and within-population heterogeneity in the gut microbiome and the associated environmental factors of wild populations is lacking. Furthermore, previous studies have limited taxonomical coverage, and knowledge about wild avian gut microbiomes is still scarce. We investigated large-scale environmental variation in the gut microbiome of wild adult great tits across the species' European distribution range. We collected fecal samples to represent the gut microbiome and used the 16S rRNA gene sequencing to characterize the bacterial gut microbiome. Our results show that gut microbiome diversity is higher during winter and that there are compositional differences between winter and summer gut microbiomes. During winter, individuals inhabiting mixed forest habitat show higher gut microbiome diversity, whereas there was no similar association during summer. Also, temperature was found to be a small contributor to compositional differences in the gut microbiome. We did not find significant differences in the gut microbiome among populations, nor any association between latitude, rainfall and the gut microbiome. The results suggest that there is a seasonal change in wild avian gut microbiomes, but that there are still many unknown factors that shape the gut microbiome of wild bird populations.